Analysis of soft tissue facial profiles of Chinese students at W.R. Supratman 1 and 2 high schools in Medan using linear and angular measurements - Hilda Fitria Lubis; Maureen Olivia (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2021)
Background: Soft tissue analysis is essential in treatment planning to ensure proportional, balanced, and harmonious soft tissue at the end of treatment. Several factors influence the variations, such as age and gender. Soft tissue profile analysis is usually studied from a lateral view. Purpose: The study aimed to determine whether there were differences in the average values of linear and angular measurement of the soft tissue profiles of the middle and lower third of the face between Chinese males and females high school students using lateral photometry. Methods: The samples were 100 lateral photographs (50 male and 50 female) of Chinese high school students at W.R. Supratman 1 and 2 in Medan. All samples were collected based on the inclusion and exclusion criteria obtained from secondary data. The linear and angular measurements were measured using Software Corel Draw 2019 and analysed statistically using an independent t-test and the Mann-Whitney test. Results: The inferior facial third, length of the lower lip, and prominence of the upper lip were, on average, greater in males, whereas in the prominence of pogonion, nasolabial angles, and nasofrontal angles were greater, on average, for females. Conclusion: There were significant gender differences in Chinese high school students in the inferior facial third, length of the lower lip, prominence of the upper lip, nasolabial angle, and nasofrontal angle, whereas there is no significant difference between genders in the prominence of the pogonion.